Safety assessment of antibiotic and probiotic feed additives for Gallus gallus domesticus. Issue 1 (December 2017) - Neveling, D.; Emmenes, L.; Ahire, J.; Pieterse, E.; Smith, C.; Dicks, L.
Abstract Antibiotics in feed select for resistant strains and is thus a threat to human health. In this study, the effect of a multi-strain probiotic and antibiotics on the growth and health of broilers was studied. Equal numbers of broilers received on a daily basis either a multi-strain probiotic or a combination of sulphadiazine, colistin and trimethoprim, whereas the control group received standard feed. The villi of immature broilers (19 days old) administered antibiotics had a larger surface area and their lymphocyte and basophil counts were higher compared to broilers from the probiotic and control groups. The cecal microbiomes of mature broilers (29 days old) that received probiotics had higher levels ofEnterobacteriaceae, but lower numbers of Clostridiales, Brucellaceae, Synergistaceae, Erysipelotrichaceae andCoriobacteriaceae compared to the antibiotic-treated group. A decline in the bioluminescence ofListeria monocytogenes observed for broilers on probiotics suggested that the probiotic may be used to control bacterial infections. No significant differences in total red blood cell, haemoglobin and haematocrit content, and mean values for corpuscular volume, corpuscular haemoglobin and corpuscular haemoglobin numbers were recorded amongst broilers from the different treatment groups. This study provides valuable information on the health and performance of broilers when administered probiotics and antibiotics as additives.